Dolphin-complab: a virtual compilers laboratory - Matos, Paulo (2003)
The goal of this paper is to present the Dolphin-COMPilers LABoratory (COMPLAB), an integrated environment conceived for the investigation, teaching, development and use of compilers. It employs Web technologies to make available a virtual laboratory containing a set of functionalities to: implement, analyze, test, evaluate and simulate compiler routines. This environment aims to support the classes of Language Processors of the graduate and post-graduate levels of the Computer Science courses, inside and outside of the classroom. The environment, reachable using a simple Web browser (connected to the Internet), should supply three distinct levels of access that correspond to three distinct types of users: conventional users, that can access to the laboratory to work on the projects where they are registered using the tools supplied by the DOLPHIN-COMPLAB; the project coordinators responsible for the management of the project (define the goals, choose tools and components, manage the users of the project, …); and the main coordinators that are responsible for the laboratory (registration of projects, integration of components, laboratory cleanness, etc). A conventional user has access to a several tools that support the two main stages of the compilers development process: the implementation and test. The functionalities supplied for the implementation allow to develop, modify and change the compiler components and the compiler structure. To support the test and evaluation of the compilers, it is supplied an integrated development environment where the users can analyze the behavior of the several compilation tasks and measure the performance of the compiler.